Metodologi Tafsir Bi Al-Ra’yi Perspektif Nashr Hamid Abu Zayd - Hidayat, Muhammad Taufiq; Matondang, Husnel Anwar; Muhammad Ziyad Ulhaq (Al-Aqwam: Jurnal Studi Al-Quran dan Tafsir, 2024)
This research aims to examine the methodology of using tafsir bi al ra'yi in detail, where most people only discuss the theory of tafsir bi al ra'yi. The methodology used in this research is qualitative with a library research type of research. The research that serves as a comparison to this research is a journal by Muhammad Shabrun Algifari with the title "A Glance at Tafsir Bi Al-Ra'yi" which discusses the problems, history and limitations of tafsir bi al-ra'yi. And in this research we will discuss the methodology of tafsir bi al ra'yi from the perspective of Nasr Hamid Abu Zayd as the novelty of this research. The results of this research are; According to Nasr Hamid Abu Zayd, to reveal the implied meaning of a text, you must use ta'wil rather than tafsir, because the meaning of ta'wil is broader than tafsir. According to him, the most accurate methodology for interpreting the Koran is the language analysis method. The method that Nasr Hamid Abu Zayd uses in interpreting the Koran is; Determine the problem in the verse textually, then relate it to history contextually. Compare with other related verses, and analyze them using linguistic methods by looking at three aspects in the analysis of Arabic language, namely; 'adad syarth, fi'il syarth, and answered syarth. Conclude and issue a fatwa based on analysis.